Lee Citrus Hybrid - L.K. Jackson; Stephen H. Futch (EDIS)
Lee is one of the released citrus hybrids arising from a cross of Clementine mandarin by Orlando tangelo made by Gardner and Bellows in 1942 at the United States Department of Agriculture Laboratory in Orlando. It was officially released as a new variety in 1959 but has never attained important commercial status. The fruit is 3/4 tangerine and 1/4 grapefruit and most closely resembles a tangerine or tangelo. There has been renewed interest in Lee following the freezes of the 1980's since the fruit matures early and the trees are fairly cold hardy. This document was published first time Sept. 1993.